Genetic surveillance and crime control social, cultural and political perspectives - Machado, Helena; Granja, Rafaela (Routledge, 2022)
"Genetic Surveillance and Crime Control presents a new empirical and conceptual framework for understanding trends of genetic surveillance in different countries in Europe and in other jurisdictions around the world. The use of DNA or genome for state-level surveillance for crime governance is becoming the norm in democratic societies. In the post-DNA, contemporary modes of criminal identification are gradually changing through the increasing expansion of transnational sharing of DNA data, along with the development of highly controversial genetic technologies that pose acute challenges to privacy and generate fears of discrimination, racism and stigmatization. Some questions that guide this book are: How is genetic surveillance in the governance of crime intertwined with society, ethics, culture, and politics? What are the views and expectations of diverse stakeholders -scientists, police agencies, and non-governmental organizations? How can social sciences research about genetic surveillance accommodate socio-cultural and historical differences, and be sensitive to specificities of post-authoritarian societies in Europe? Taking an interdisciplinary approach focused on challenges to genetic privacy, human rights and citizenship in contemporary societies , this book will be of interest to students and scholars of social studies of science and technology, sociology, criminology, law and policing, international relations and forensic sciences"--